2014
DOI: 10.1111/1462-2920.12500
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific corrinoids reveals corrinoid modification in dechlorinating microbial communities

Abstract: Cobalamin and other corrinoids are essential cofactors for many organisms. The majority of microbes with corrinoid-dependent enzymes do not produce corrinoids de novo, and instead must acquire corrinoids produced by other organisms in their environment. However, the profile of corrinoids produced in corrinoid-dependent microbial communities, as well as the exchange and modification of corrinoids among community members have not been well studied. In this study, we applied a newly developed LC/MS/MS–based corri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 58 publications
(119 reference statements)
2
102
0
1
Order By: Relevance
“…15 N-ammonium chloride was purchased from Cambridge Isotopes Laboratories. 5-OHBza was synthesized as previously described (33 12 , and Factor A were purified as described (34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 N-ammonium chloride was purchased from Cambridge Isotopes Laboratories. 5-OHBza was synthesized as previously described (33 12 , and Factor A were purified as described (34).…”
Section: Methodsmentioning
confidence: 99%
“…The UV-Vis spectra were collected during HPLC analysis using Agilent ChemStation software. Samples were further characterized on an Agilent 6410 liquid chromatograph-triple quadrupole mass spectrometer using an Agilent Zorbax SB-Aq column to identify cobamides based on their characteristic transitions and retention times (34). For corrinoid extracts from strains grown in 15 NH 4 Cl, the MS method was modified to detect the Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Studies with Dhc strain 195 revealed that TCE reductive dechlorination was only sustained by DMB-cobamide (Cba), 5-MeBzaCba and 5-OMeBza-Cba, but not by Bza-Cba, 5-hydroxybenzimidazolyl-cobamide (5-OHBza-Cba or factor III) or phenolic cobamides (Phe-Cba and p-Cresol-Cba) (Yi et al, 2012;Men et al, 2014b). Apparently, the cobamide lower base (Figure 1) determines whether Dhc can or cannot use chlorinated hydrocarbons as electron acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Corrinoids are a family of related molecules that include vitamin B 12 and are obligatorily or facultatively utilized by many organisms, including animals, algae, and bacteria (10,11). Corrinoids comprise a porphyrin ring that coordinates a central cobalt ion (12) with variable upper and lower axial ligands (13,14). The most well-studied corrinoid variants are cobalamins, with dimethylbenzimidazole (DMB) as the lower axial ligand, and which include vitamin B 12 (or cyanocobalamin, Cbl), which has a CN group as the upper axial ligand.…”
mentioning
confidence: 99%